Identifikasi Zona Agroekologi dan Kesesuaian Lahan Komoditas Mangga Arumanis (Mangifera indica L.) di Kabupaten Probolinggo - Apong Sandrawati; Abraham Suriadikusumah; Ajeng Dwi Yuningtyas (Fakultas Pertanian Universitas Padjadjaran, 2017)
Probolinggo district is the one of the largest mango producing in Indonesia. Mango (Mangifera indica L.) is a fruit with a very good potential to be developed. Production of mango in Probolinggo district was decreased. The aim of this research to determine the land suitability for arumanis mango in Probolinggo district. This research has conducted in April untill May 2016 at Probolinggo district and Faculty of Agriculture, University of Padjadjaran. Land evaluation based on agroecological zone are slopes, drainage, moisture and temparature. Sampling spot are used composite sampling based on agroecological zones and data analysis using descriptive and comparative methods. Results of the research suitability of arumanis mango land in Probolinggo district there are three classes which enough suitable (S2), marjinal suitable (S3), and not suitable forever (N2) land suitability class with a major limiting factor slope, texture, temperature, effective depth and precipitation. Based on the result, in conclusion zone I, II and III with 69.851,36 Ha and 54,58 % is suitable for development arumanis mango in Probolinggo district.Keywords: arumanis mango, agroecological zones, land suitability